Space charge behavior in polymeric insulating materials under DC stress and pre-breakdown phenomena - Amir Izzani, Mohamed (2013)
Space charge has been recognized as an agent of insulation degradation for power transmission cable especially under high voltage dc ap1ication. It penetrates into bulk of insulating material, namely cross-linked polyethylene (XLPE), by time during dc voltage application. The increase in space change density enhances local electric field in the insulating material. In other words, the local electric field is distorted. When the field distortion reaches a critical value, dc breakdown of the insulating material will occurs, causing a catastrophic damage to the cable. Therefore, it is important to understand space charge inside an insulating material in order to improve the reliability of next generation power cables.